Aerodynamic Performance Analysis of Tandem Savonius Wind Turbines Influenced by Lateral Gap from Adjacent Wall - Audha Fitrah Aulina; Haning Hasbiyati (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2026)
This research investigates the performance of the Savonius wind turbine through a two-dimensional Computational Fluid Dynamics (CFD) analysis, employing the realizable k − ε turbulence model with enhanced wall treatment. The primary objective is to examine how variations in the gap-to diameter ratio (G/D)—defined as the distance between the centers of the turbines relative to the blade diameter—affect the aerodynamic behavior and performance of a tandem Savonius wind turbine configuration. In this study, three G/D ratios are analyzed, namely 1.75, 2, and 2.25, under a uniform freestream wind velocity of 7 m/s. The simulation results indicate that flow deflection between the turbines induces opposite rotational directions: the fore turbine rotates counterclockwise, while therear turbine rotates clockwise, particularly at higher tip speed ratios. Performance analysis reveals that the fore turbine achieves its maximum efficiency at a G/D ratio of 2, whereas the rear turbine performs optimally at a G/D ratio of 1.75.